Analysis of the electrical characteristics and surge protection of EHV transmission lines supported by tall towers - Pinto, Andre Jinno G.; Costa, Eduardo Coelho M. [UNESP]; Kurokawa, Sergio [UNESP]; Monteiro, Jose Humberto A.; Franco, Jorge Luiz de; Pissolato, Jose (Elsevier B.V., 2014)
The electrical characteristics of a new 280-m-tall transmission line are analyzed. The geometrical distance of the phases, wires height and physical structure of the line are intrinsic associated with its electrical performance in steady state as well as in transient conditions. Thus, a frequency-domain analysis is proposed comparing the longitudinal and transversal electrical parameters calculated from the tall transmission line with the same parameters obtained for a conventional 440-kV line. An adapted method for the mutual parameters is proposed to calculate the shunt capacitances considering two dielectrics between the wires and ground (air and forest), taking into account that the new transmission system has not a corridor, as usually observed in conventional lines. A second analysis is performed based on both lines modeling and time-domain simulations using the EMTP. Electromagnetic transient simulations from an atmospheric impulse shows that the tall transmission line has a major transient overvoltage than a conventional line. In sequence, an alternative surge protection is proposed using metal-oxide arresters connected directly at the phases, in parallel with the line insulators. The main objective of this technical report is to evaluate the electrical characteristics of the new transmission system using tall structures and, by this means, to highlight the possible variations concerning its operation and transient response. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Tall transmission towers; Frequency-domain analysis; Electromagnetic transients; Lightning performance; Surge arresters